2022
DOI: 10.1097/sle.0000000000001037
|View full text |Cite
|
Sign up to set email alerts
|

Role of Indocyanine Green Fluorescence Imaging in Minimally Invasive Resection of Colorectal Liver Metastases

Abstract: Indocyanine green (ICG) fluorescence imaging is an easy and reproducible method to detect hepatic lesions, both primary and metastatic. This review reports the potential benefits of this technique as a tactile mimicking visual tool and a navigator guide in minimally invasive liver resection of colorectal liver metastases (CRLM). PubMed and MEDLINE databases were searched for studies reporting the use of intravenous injection of ICG before minimally invasive surgery for CLRM. The search was performed for public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…However, the indications for the hepatic metastasectomy of colorectal origin are still evolving. Nevertheless, up to 1/3 of patients undergoing the curative resection of colorectal hepatic metastases will have R1 resections (<1 mm resection margin) or residual disease due to the inability to properly detect intraoperatively [ 102 ]. This can severely impact disease-free survival and overall survival.…”
Section: Current Uses Of Icg In Colorectal Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the indications for the hepatic metastasectomy of colorectal origin are still evolving. Nevertheless, up to 1/3 of patients undergoing the curative resection of colorectal hepatic metastases will have R1 resections (<1 mm resection margin) or residual disease due to the inability to properly detect intraoperatively [ 102 ]. This can severely impact disease-free survival and overall survival.…”
Section: Current Uses Of Icg In Colorectal Surgerymentioning
confidence: 99%
“…There have been several reports on the use of ICG for intraoperatively localizing colorectal liver metastasis. The most recent review was by Picollo et al [ 102 ] in 2022 and included 13 studies (literature search through April 2021). The authors reported a wide variation in the timing of ICG administration (1 to 14 days preoperatively) as well an average detection rate of metastases with ICG of 79.03% (range: 57.6–100) compared to 95.97% (range: 93.3–100%) with intraoperative ultrasound.…”
Section: Current Uses Of Icg In Colorectal Surgerymentioning
confidence: 99%
“…For example, ICG fusion imaging could detect occult small-sized lesions that had not been diagnosed preoperatively. In addition, ICG is effective in the real-time assessment of surgical margins by evaluating the integrity of the fluorescent rim around a colorectal liver metastases [ 87 ]. Allowing surgeons to tune intraoperatively to specific fluorescence detection bands in the NIR-I/II wavelength region should allow for visualization to be tailored to specific surgical tasks.…”
Section: Nir-ii Fluorescence and Cancer Treatmentmentioning
confidence: 99%
“…Before the first laparoscopic hepatectomy reported in1990s, patients can only choose open hepatectomy as surgical treatment of liver tumor (6). As time goes on, the benefits of laparoscopic were discovered by surgeon such as less venous bleeding, more accessible to the liver inside the rib cage, and better magnified view (7).After the 2nd International Consensus Conference on Laparoscopic Liver Resection, laparoscopic liver resection has been spread explosively in North America, Europe and East Asia (8).At the same time many surgeons start to use Indocyanine Green Fluorescence Imaging as a tactile mimicking visual tool (9).…”
Section: Introductionmentioning
confidence: 99%